Universal design for learning: perceptions of faculty and students at a northeastern community college - Gawronski, Michael E., author; Kuk, Linda, advisor; Anderson, Sharon, committee member; Sample, Pat, committee member; Lombardi, Allison, committee member (Colorado State University. Libraries, 2014)
To examine community college faculty and student attitudes toward and actions associated with inclusive instruction based on Universal Design for Learning (UDL) principles and practices, two online surveys, the Inclusive Teaching Strategies Inventory (ITSI) and the Inclusive Teaching Strategies Inventory-Student (ITSI-S), were administered at a medium-sized Northeastern public Community College (n=449). The ITSI and ITSI-S contain six subscales representing the following constructs: (a) accommodations, (b) accessible course materials, (c) course modifications, (d) inclusive lecture strategies, (e) inclusive classroom, and (f) inclusive assessment. A series of Multivariate Analyses of Variances (MANOVA's) were performed to identify predictors of these attitudes and actions among faculty and students. Results found significant differences among faculty (N=179) in overall action scale scores based on age and ethnicity. However, similar analyses conducted on students were not significant. Results of the current study respond to the gap in the literature by examining inclusive instruction based on universal design for learning in the community college environment. Discussion, implications of these findings and recommendations for future research were discussed.
Keywords: universal design for learning; college faculty; college students; college students with disabilities; diversity; inclusive teaching